Damage sensing using a mechanophore crosslinked epoxy resin in single-fiber composites. (26th May 2020) - Woodcock, Jeremiah W.; Sheridan, Richard J.; Beams, Ryan; Stranick, Stephan J.; Mitchell, William F.; Brinson, L. Catherine; Gudapati, Vamshi; Hartman, David; Vaidya, Amol; Gilman, Jeffrey W.; Holmes, Gale A.
Abstract: Fiber fracture is a major contributor for the initiation of failure in fiber-reinforced polymer composites. The purpose of this study was to identify where damage occurs when a fiber fractures in a composite. Because this dynamic event occurs in less than 100 1ns, obtaining experimental evidence has been prohibitively difficult. Here, we report a novel method using a model composite, comprised of a spirolactam-based mechanophore-functionalized epoxy resin with a single embedded glass fiber. The ductile epoxy matrix is loaded under tension, which transfers load through interfacial shearing to the embedded brittle fiber, causing the fiber to break into segments. Fluorescence lifetime imaging microscopy (FLIM) is used to visualize regions of mechanophore activation and quantify changes in the dye's local environment such as relaxations on the nanosecond timescale. FLIM of these single fiber fragmentation test (SFFT) samples reveals localized damage zones in the epoxy matrix, not only at the point of fiber fragmentation, but also at distances remote from the fracture site that extend radially into the matrix up to two fiber diameters. The average mechanophore lifetime in the bulk epoxy is (1.5 ± 0.5) ns and in the damage regions is (0.75 ± 0.15) ns. This new data reveals the existence of polymer matrix yielding, which occurs during the fiber fracture event, and agrees with a dynamic model that predicts yielding behavior in the matrix during fracture. These results suggest that the damage from fiber fracture is more extensive than previously recognized. This new approach can be used to elucidate damage in other mechanical tests. The subsequent insights into composite damage mechanisms promises to dramatically accelerate the development of tough, durable, and damage tolerant composites.